2022
DOI: 10.1002/ehf2.13842
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study on the treatment of chronic heart failure with a novel D‐shant atrium shunt device

Abstract: Background Atrial septal shunt devices might improve hospitalizations and also prognosis in heart failure with increased pulmonary pressures due to left heart diseases. In recent years, atrial shunt devices have been used for the treatment of chronic heart failure, but there remains a lack of clinical experience. This study aimed to analyse the therapeutic effect of a novel type of atrial shunt on chronic heart failure. Methods and results From May 2020 to September 2020, six patients who were diagnosed with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In theory, a signi cant decrease in LAP with no volume overload of the right chamber may lead to improvement of LVEF [23]. All the studies included in our meta-analysis used echocardiography to evaluate LVEF with the exception of the D-shant study, which used MRI [22]. Considering that the imaging examination modality used may affect the results, we removed this study and found that LVEF still showed an increasing trend after ISDs implantation (MD 2.53%; 95% CI -0.30, 5.37; P = 0.08; I 2 = 0).…”
Section: Discussionmentioning
confidence: 99%
“…In theory, a signi cant decrease in LAP with no volume overload of the right chamber may lead to improvement of LVEF [23]. All the studies included in our meta-analysis used echocardiography to evaluate LVEF with the exception of the D-shant study, which used MRI [22]. Considering that the imaging examination modality used may affect the results, we removed this study and found that LVEF still showed an increasing trend after ISDs implantation (MD 2.53%; 95% CI -0.30, 5.37; P = 0.08; I 2 = 0).…”
Section: Discussionmentioning
confidence: 99%
“…[222,223] Therefore, the rational combination of natural and synthetic materials and the choice of preparation strategy are crucial for the preparation of artificial small blood vessels by electrostatic spinning. [205] Copyright 2022, The Authors, published by John Wiley and Sons on behalf of European Society of Cardiology.…”
Section: Engineering-based Techniquesmentioning
confidence: 99%
“…Down: the photos of D-shant atrium shunt device. Reproduced with permission [205]. Copyright 2022, The Authors, published by John Wiley and Sons on behalf of European Society of Cardiology.…”
mentioning
confidence: 99%